Redesain Gerobak Martabak Menggunakan Antropometri dan Quality Function Deployment - Alfian, Muhammad Iqbal; , Etika Muslimah ST, MM, MT (2016)
Indonesia has many culinary business using carts, for example martabak. Cart used by the seller martabak is simple cart with stainless steel, aluminum, wood, glass, and made with the approximate size pickup without any consideration of the science. Through anthropometric approach and Quality Function Deployment (QFD), the design of the cart will be good and according to customer needs. Anthropometric approach used to design dimensions of the cart and QFD used to meet consumer needs for design of the cart. Anthropometric data used in the design of the cart are elbow span, fore arm span, high above hand grip, hip height. Consumer needs based on QFD is divided into four. Ergonomics, performance, materials, and designs. The consumer needs come from the questionnaire with consumers and will be processed in a House of Quality (HOQ). Carts design are made to be referring to the anthropometric dimensions and the voice of the customer in QFD. Martabak cart product prices can be determined by using the Cost of Production (HPP). Based on the HPP will know the price cost of sales is the reference price of one the martabak cart.